Pengaruh Pendekatan Pembelajaran TaRL (Teaching at Right Level) dalam Meningkatkan Hasil Belajar Peserta Didik Pada Pelajaran Matematika Di SMKN 8 Surabaya - Yustafudin Arif (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2024)
The research was motivated by the problems of interest, motivation and learning outcomes of students regarding mathematics lessons in class There are those who have low, medium and high ability to understand the material and different learning styles, including visual, auditory and kinesthetic learning styles. The learning needs of these students have also not been met. So that from these problems abilities and learning styles can influence student learning outcomes. The reason behind the researchers conducting this research was the low interest in learning of students in mathematics subjects. Among the 27 students, there were only 14 (52%) students who liked mathematics and 13 (48%) students who did not like mathematics. This research aims to determine the improvement in student learning outcomes through the TARL (Teaching at Right Level) learning approach. This research uses the classroom action research (PTK) method with a quantitative approach and data collection techniques using the results of the students' pretest and posttest. The material used in this research is opportunity material in Mathematics Lessons.